Kościół pw. św. Teresy od Dzieciątka Jezus w Pełczynie, gm. Wołów. Przyczynek do badań wiejskiej architektury sakralnej na Śląsku - Mruczek, Roland
The work is a contribution to research on the Silesian provincial sacred architecture. It contains the results of archaeological and architectural research on the foundation parts of the church under the invocation of St. Teresa of the Child Jesus at Pełczyn, Wołów commune, carried out on the occasion of the drainage of its perimeter walls. They allowed for the presentation of the chronological stratification of individual parts of the building, based on an analysis of the technique and technology of construction, as well as typological analyses. The temple belongs to a very large group of rural churches in Silesia, of late medieval origin, significantly rebuilt later.
Keywords: Silesia; church; Pełczyn; chronolical stratification